Laboratory Investigation of Poultry Pasteurellosis - Nsanbayeva G. T.; Pulotov F. S. (American Journal of Biodiversity, 2026)
This article presents the results of biological and bacteriological investigations of avian pasteurellosis under laboratory conditions, including the inoculation of pathological materials into meat-peptone broth (MPB) culture medium and microscopic examination findings. The scientific research was conducted in May 2026 during a field visit to Tayloq district of Samarkand region. The study was carried out under the supervision of F.S. Pulotov in the Microbiology Laboratory of the Veterinary Research Institute located in this district. During the study, a chicken brought from a farm was subjected to pathological-anatomical examination under laboratory conditions. Samples were collected from the parenchymal organs and inoculated into meat-peptone broth culture medium in compliance with biosafety regulations. After incubation, smears were prepared, stained using the Gram staining method, and examined microscopically.